Israel's long war with Hezbollah : military innovation and adaptation under fire - Marcus, Raphael D. (Georgetown University Press, 2018)
This book provides the first comprehensive military history of the decades-long conflict between Israel and Lebanon's Hezbollah. It begins in 1985 during the Israeli occupation of southern Lebanon, includes the Second Lebanon War (a.k.a. the July War) in 2006 and aftermath, and brings the story up to the present. Raphael Marcus conducted extensive research in primary sources in both Hebrew and Arabic and conducted dozens of interviews with Israeli military participants. A second contribution of the book is that it assesses both strategic and operational military learning and adaptation by each side, or lack thereof, during the guerilla and counterguerilla campaigns. His conclusions illustrate the complexity and messiness of military adaptation under fire. It tells the story of slow strategic adaptation and disjointed operational adaptation by the Israeli Defense Forces, where civil-military relations, regional and geostrategic factors, institutional dynamics, domestic pressures, and organizational culture each hindered change. An Afterword in the book discusses adaptation on both sides since the 2006 war and Hezbollah's involvement in the war in Syria. Tensions between Israel and Hezbollah have once again heated up in fall 2017, making this a timely book.